2022
DOI: 10.1021/acs.langmuir.2c00120
|View full text |Cite
|
Sign up to set email alerts
|

Electron Doping of Semiconducting MoS2 Nanosheets by Silver or Gold Nanoclusters

Abstract: Semiconducting two-dimensional (2D) materials have potential applications as ultrathin optoelectronic materials. Therefore, being able to precisely modulate the band gap is useful to improving their applicability. Electron doping of the semiconducting materials is one of the successful techniques used to modulate their band gap. Silver nanoclusters (AgNCs) or gold nanoclusters (AuNCs) a few nanometers in size can generate a high density of highly energetic hot electrons with relatively long lifetimes when phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…The existence of these unwanted signals degrades the quality of optical microscopic images. The photoluminescence (PL) signal from MoS 2 forms a constant background pattern in the fluorescence image (Figures d, S4, and S5), thus reducing the precision of localizing the photoswitchable dye molecule, AF647, labeled on the adsorbed HAFs at different structural features. The reconstructed dSTORM images in the presence of the constant background pattern (Figure g,j) include many falsely localized molecular positions.…”
Section: Resultsmentioning
confidence: 99%
“…The existence of these unwanted signals degrades the quality of optical microscopic images. The photoluminescence (PL) signal from MoS 2 forms a constant background pattern in the fluorescence image (Figures d, S4, and S5), thus reducing the precision of localizing the photoswitchable dye molecule, AF647, labeled on the adsorbed HAFs at different structural features. The reconstructed dSTORM images in the presence of the constant background pattern (Figure g,j) include many falsely localized molecular positions.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, two-dimensional layered materials with ultrathin structures have shown good application prospects in lubrication, optics, electrochemistry, and catalysis due to their unique structures and excellent properties. , Many studies have shown that two-dimensional layered materials have an extremely high-load-bearing capacity and can easily enter the friction contact area due to their ultrathin thickness. These materials remarkably affect friction and wear properties. , Two-dimensional MoS 2 nanosheet has the characteristics of a two-dimensional layered material and strong adsorption properties between the sulfur element exposed on the surface of MoS 2 and the metal surface. Thus, a tribochemical reaction film can be easily formed on the friction surface, which is ideal for high-performance lubricant additives.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, two-dimensional layered materials with ultrathin structures have shown good application prospects in lubrication, optics, electrochemistry, and catalysis due to their unique structures and excellent properties. 1,2 Many studies have shown that two-dimensional layered materials have an extremely high-load-bearing capacity and can easily enter the friction contact area due to their ultrathin thickness. 3−6 These materials remarkably affect friction and wear properties.…”
Section: ■ Introductionmentioning
confidence: 99%